Model of Web-Based Application “Glide” As Learning Media and Knowledge Sharing Tool of Teachers in Post-Pandemic Era - Ryan Oktapratama; Dylmoon Hidayat (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
One of the adaptations that are being carried out in schools in Indonesia in the post-pandemic era is the implementation of online learning models and mixed learning. However, the challenge that arises is that for teachers today more effort is needed to create activities that can be used in this new situation. One application that can accommodate the need to store various types of teaching materials from all teachers in various schools is a web-based application such as Glide. The purpose of this study is to analyze whether the Glide web-based application can be applied as a learning medium and a means of sharing knowledge for teachers in the post-pandemic period. The research method used is qualitative with the development of problem solving methods of linking. The results showed that Glide can be used as a learning medium and a means of sharing knowledge for teachers in the post-pandemic period with some notes. First, the school or teacher must design it so that the contents of the application focus on the collection of teaching materials. Second, the manipulative ability of learning media cannot be obtained through the Glide application. Third, schools need to develop plans so that the implementation of this application can run effectively.